ok, go with y = 3x+5
into the 1st
x(3x+5) = 2
3x^2 + 5x - 2 = 0
((3x-1)(x+2) = 0
x = 1/3 or x = -2 --- > you are correct
if x = 1/3, y= 3(1/3) + 5 = 6
if x = -2 , y = 3(-2) + 5 = -1
so x=1/3, y=6 OR x=-2, y =-1
I don't know how you got your values ???
I need help solving this set of equations by substitution.
xy=2
3x − y + 5 = 0
I originally used (3x+5=y) and came up with (x=.333 and x=-2) but when I substitute it into the original equation I get (y=2 and y=1) and it is wrong according to my homework. Please help me!
1 answer